Conservative Power Theory for Harmonic Voltage Responsibility Assignment - Tardivo Rodrigues, Diego [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Discussions on the different methods for sharing responsibilities regarding harmonic distortions in power grids have received wide attention in the area of power quality. This paper proposes a methodology based on Conservative Power Theory (CPT) for responsibility assignment due to the harmonic voltage distortions present at the point of common coupling. First, a theoretical basis for analyzing the orthogonal current decomposition of CPT under non-sinusoidal conditions is presented. Next, using the frequency domain, a methodology is introduced to separate the contributions of the harmonic voltage distortions in the CPT's orthogonal currents. To illustrate the application of the proposed methodology, it is simulated a real large-scale electrical system composed of an energy utility and three industrial plants connected to the same common coupling point. Finally, the results obtained are compared to other method showing the effectiveness of the proposed approach.
Keywords: Capacitors; Harmonic analysis; Harmonic distortion; Picture archiving and communication systems; Power quality; Power system harmonics; Voltage